Peculiarities of electromagnetic waves absorption in polymer magnetic nanocomposites (La,Sr)MnO₃ - Kalmykova, T.V.; Tarapov, S.I.; Neduch, S.V.; Krivoruchko, V.N.; Danilenko, I.A.; Burchovetckii, V.V.; Gurtovoj, D.G. (Functional Materials, 2012)
The results of research of the nonresonant and magnetic resonance absorption of electromagnetic waves in polymer magnetic nanocomposites (La₀.₇Sr₀.₃Mn₀.₃) in 10-40 GHz and 60-78 GHz frequency bands are presented. The absorption magnitude up to -7.5 dB at 32-35 GHz has been detected for the composite with 60 % filling and a layer thickness of 0.53 mm. The analysis of results obtained proves a high level homogeneity of magnetic nanoparticles distribution in the polymer matrix. The most probable reasons of unusually large value of the spectroscopic splitting factor, obtained by Electron Spin Resonance technique, are under discussion. The results of design of the technology and the manufacturing technique of ferromagnetic composites together with epoxy-polysiloxane polymer matrix are presented.